Effect of Uncaria tomentosa (Cat´s claw) over dendritic cells population and activation in peripheral blood of rheumatoid arthritis patients - Núñez Ponce, César (2008)
Introduction: Rheumatoid arthritis (RA) is an autoimmune disease characterized by a chronic inflammatory process within the joints. Recently, the importance of dendritic cells (DC) has been emphasized in this condition due to their remarkable ability for presenting autoantigens and for stimulating auto-reactive T-cells. The ability of Uncaria tomentosa (Cats claw), a native Peruvian plant with immune-modulating properties on the circulating dendritic cell population and on their maturation and co-stimulation capacities was assessed.Objectives: To determine subsets of myeloid and plasmacytoid dendritic cells (mDC and pDC, respectively) in patients with RA with the use of flow cytometry. To evaluate variations in the expression of HLA-DR and CD86 molecules in both subsets of DC in response to different concentrations of a hydro-alcoholic extract of Cat´s claw with 5% of pentacyclic oxindole alkaloids.Materials and methods: Peripheral blood dendritic cells were taken from RA patients and healthy controls, and they were incubated with different concentrations of Cat´s claw. Then, cells were labeled with specific monoclonal antibodies and they were separated using flow cytometry and they were analyzed with a Summit 4.3. software. Statistical analysis was performed using Friedman´s, T-student, trends and repeat measure analysis tests.Results: We found that Cat´s claw extract decreased in a dose-dependent fashion mDC population in the peripheral blood of RA patients without affecting pDC, and it also increased HLA-DR and CD86 expression on mDC.Conclusions: Cat´s claw reduced the mDC subset, while it increased HLA-DR and CD86 expression in RA patients. This is an additional mechanism for the known immune-modulating effect of Cat´s claw in chronic inflammatory conditions.